UPAYA PENINGKATAN HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK MENGGUNAKAN BILAH BERJENJANG PADA SISWA KELAS V SD NEGERI 1 GANDASULI KECAMATAN BOBOTSARI KABUPATEN PURBALINGGA 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
Is using a tiered blade tools to improve learning outcomes in the long jump squat styleclass V students of SD Negeri 1 Gandasuli?. This study aims to improve the learn-ingoutcomes of the long jump squats using the bar-style tiered in class V SD Negeri 1Gandasuli Purbalingga 2013. This research is a class act consisting of two cycles, witheach cycle consisting of four stages: planning, action, observation, and reflection. Theresearch was conducted in SD Negeri 1 Gandasuli District Bobotsari Purbalingga.Subjects were students of class V, amounting to 24 students. Conclusions based on theresults of the data analysis it can be concluded that the use of a tiered blade on the materiallong jump squat style can improve student learning outcomes, so the researcherssuggest that the need for the ability to think creatively on Penjasorkes teachers in theuse of media / learning tools to solve problems, and use of assistive devices Tieredblades can be used as an alternative in the long jump address learning outcomes thatresult thoroughness style squat further than expected / lot below the minimumcompleteness criteria (KKM) is equal to 7.5.